Effects of Parenting Styles on Children’s Psychological Development and Their Impact on Child Abuse - María Camila Santana Pérez; Deilis Inés Vega Ospino (RHS Revista Humanismo y Sociedad)
Child abuse manifests in various forms within families and has a profound impact on children’s psychological development. This study examines parenting styles to identify patterns that foster healthy psychological development and those that may lead to child abuse. To achieve this, a conceptual review of the issue was conducted, drawing on data from previous research to bridge the reality of child abuse with relevant concepts and theoretical framework. Our analysis revealed that parenting habits play a critical role in shaping children’s social skills, academic performance, and their capacity to build healthy relationships. Authoritarian and neglectful parenting styles may cause emotional and behavioral problems, whereas democratic parenting styles support comprehensive development, resilience, and a reduction in child abuse rates. The findings highlight the importance of promoting healthy parenting habits to reduce child abuse, enhance children's psychological well-being, and improve their quality of life.